EVALUASI MANAJEMEN LAYANAN TEKNOLOGI INFORMASI DENGAN FRAMEWORK ITIL V4 PADA SISTEM E-PRESENSI BKPSDM KABUPATEN CIAMIS - Dewi Puspita Sari; Insiroh Amaliana; Lauren Nugraha; Sendy Seftiawan; Helmy Dzulfikar (Department of Science and Technology Ibrahimy University, 2025)
The Ciamis Regency BKPSDM has implemented a mobile-based electronic attendance system (e-attendance) to improve the discipline of civil servants. This study aims to evaluate the IT service management of the e-attendance system using the ITIL V4 framework. The evaluation focuses on eight service management practices: Availability, Incident, Problem, Service Desk, Service Level Management, IT Asset, Monitoring & Event, and Service Request Management. This study uses a mixed method, collecting quantitative data through questionnaires to civil servants who are educators and qualitative data through interviews with the BKPSDM IT Team. The main objectives are to measure the level of maturity, analyze the gap between user perceptions, internal realities, and ideal conditions according to ITIL, and provide strategic improvement recommendations. The results of the study show a significant perception gap, namely that civil servants assess services at Level 4 (Quantitatively Managed), while the reality of the IT Team's internal processes is mostly at Level 2 (Managed). This gap arises because user satisfaction is based on rapid problem resolution, while the internal processes lack formal documentation and standardization, such as a ticketing system and internal SLAs. Consequently, the recommendations prioritize establishing structured procedures and formal controls to elevate the maturity of the core service practices found to be crucial. Recommendations are focused based on their level of urgency, namely on improving Incident Management, Service Level Management, and Service Request Management to close this gap.